Tugas Prarancangan Pabrik Metil Akrilat Dari Metanol dan Asam Akrilat dengan Proses Esterifikasi Kapasitas 30.000 Ton/Tahun - Perdana, Wira Yudha, Emi Erawati, S.T., M.Eng, Mujiburohman, S.T., M.T., Ph.D (2016)
Methyl acrylate (CH2CHCOOCH3) is a chemical used as a raw material for the production of polymers (polyacrylate). These polymers are used as the manufacture of paints (coatings), adhesives and binders for leather industry, paper and textiles as well as raw materials for polymers of acrylic fiber. Raw materials used in the production process of methyl acrylate is acrylic acid and methanol. The method used in the manufacture of methyl acrylate is by esterification of acrylic acid and methanol with a temperature of 80°C and a pressure of 1 atm in the liquid phase is reacted in a stirred tank flow reactor mounted on a series of isothermal conditions. The factory requires raw materials acrylic acid of 3750,00 kg/hour and methanol amounted to 3782,20 kg/hour. Sulfuric acid as a catalyst is needed as much as 1856,06 kg/hour with a total weight of water as an impurity of 81,44 kg/hour. For utilities, the water used as 497,248,88 kg/hour. As for the fuel needed as much as 265.61 L/hour, amounting to 178,33 kW of electricity and steam needs of 20.049,23 kg/hour. The factory is planned to stand 2020. Methyl acrylate plant will be established with a capacity of 30,000 tons per year in the industrial estate in Cilegon, Banten and a land area reaches 5830 m2. Fixed capital plant or it called as fixed capital investment (FCI) Rp. 609.104.713.279, while the working capital of Rp. 116.281.332.356. Total production cost per year is Rp. 472.260.614.815. Economic evaluation showed that: percent return on investment (ROI) before taxes 24,21% and 18,15% after tax, pay out time (POT) before tax and after tax 2,92 years to 3,55 years, break even point (BEP) 50,05%, shut down point (SDP) 22,76%, and the discounted cash flow (DCF) 30,23%. From the results of the calculation data of economic evaluations, it feasible to set up factories in Indonesia.